Verbal instructions affect reactive strength index modified and time-series waveforms in basketball players - Sánchez-Sixto, A.; McMahon, J. J.; Floría, P. (Sports Biomechanics, 2024)
This study aimed to determine the effects of different verbal instructions, intended to affect the countermovement jump (CMJ) execution time, on the reactive strength index modified (RSIMod) and the time-series waveforms. Thirteen male basketball players performed six CMJs on a force plate with two different verbal instructions: -jump as high as possible- (CMJhigh) and -jump as high and as fast as possible- (CMJfast). Force-, power-, velocity-, and displacement-series waveforms, RSIMod and jump height were compared between conditions using statistical parametric mapping procedures. CMJfast showed greater values in RSIMod (p =0.002) despite no differences in jump height (p =0.345). Unweighting force (between 18% and 33% of total time) was lower in the CMJfast compared to CMJhigh. Larger force (between 53% and 63% of total time), velocity (between 31% and 48% of total time) and power (between 43% and 56% of total time) were found in the CMJfast compared to CMJhigh. These findings suggest that commanding athletes to jump as high and fast as possible increases rapid force production. Additionally, the results highlight the relevance of the countermovement phase in jumping and show that RSIMod could increase without power output modifications during propulsion, despite previous studies having reported positive associations between RSIMod propulsion power.